Artificial intelligence as a tool for Alzheimer’s treatment: Implications and future prospects in Jordan Harrison’s Marjorie prime - Albalawi, Sabrya H. (Edelweiss Applied Science and Technology, 2025)
In his play Marjorie Prime, Jordan Harrison engages in a critical dramatisation of artificial intelligence as a means of recovery in the treatment of victims of Alzheimer's disease, whereby artificial intelligence plays a therapeutic role by the creation of a holographic shadow of the people the Alzheimer's victim forgot (Primes). Looking at how the three concepts of AI, memory, and identity might converge, the story provides a basis to review real-life uses of technology like chatbots, virtual friends, and robotic assistants. The literary-critical approach shows that the cognitive reinforcement, emotional distress mitigation, and increased social interaction with others, especially the ageing population, can be elevated with the help of AI technologies. However, there is an ethical issue of using secondary sources of data and algorithmic misinterpretation of them: created memories, identity confusions, and ousting human caregivers. Such imaginative situations portray the increasing difficulties in cognitive-therapeutic AI. The friendly taping over of personal history dramatises the promise of therapeutics and the artificiality of rebuilding history. Memory care necessitates a culture of ethical calibration of AI, whereby its use contributes to improving the fabric of authenticity, autonomy, and relational aspects of human memory and does not inflict a loss.